2012
DOI: 10.1029/2011gb004228
|View full text |Cite
|
Sign up to set email alerts
|

Global importance, patterns, and controls of dissolved silica retention in lakes and reservoirs

Abstract: [1] Lentic water bodies (lakes and reservoirs) offer favorable conditions for silica (SiO 2 ) burial in sediments. Recent global estimates suggest that (1) lentic SiO 2 trapping is a globally important SiO 2 flux, and (2) through reservoir construction, humans have dramatically altered river dissolved SiO 2 (DSi) transport and coastal DSi delivery. However, regional to global scale patterns and controls of DSi removal in lentic systems are poorly constrained. Here we use 27 published lake and reservoir DSi bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 62 publications
2
45
0
Order By: Relevance
“…Our approach differs from SiRReLa (Harrison et al 2012) in two key ways. Firstly, our results are not spatially explicit.…”
Section: Lake Si Accumulation: Uncertainties and Implications For Thementioning
confidence: 99%
See 2 more Smart Citations
“…Our approach differs from SiRReLa (Harrison et al 2012) in two key ways. Firstly, our results are not spatially explicit.…”
Section: Lake Si Accumulation: Uncertainties and Implications For Thementioning
confidence: 99%
“…The only attempt to date (Harrison et al 2012) used 27 Si mass balances, including 24 of those compiled here (different inclusion criteria) to calibrate the SiRReLa model, but did not explore the use of AR BSi or C BSi data or potential links between catchment processes and Si accumulation. Our analysis demonstrates that core-based accumulation rates are unsuitable for upscaling (''BSi accumulation rates''), that surface sediment BSi concentrations are unrelated to accumulation rates (''Si surface sediment concentrations'') and that inclusion of catchment parameters does not help create scalable models, so only 30 mass-balance based sedimentation rates (''Si mass-balance studies'') remain.…”
Section: Lake Si Accumulation: Uncertainties and Implications For Thementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, scientific AEMs can help to close mass balances of essential elements such as carbon, nitrogen and phosphorus and thereby allow quantifying the role of aquatic systems in national and global carbon and nutrient budgets (Robson et al 2008;Harrison et al 2012). Keeping track of mass balances can also provide help in answering stoichiometric questions (Giordani et al 2008;Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Classical colloid studies on model systems, summarized in the discussion section below, have shown significant adsorption of aluminium species on titania surfaces at these concentrations [8][9][10][11] and this paper considers the influence on photocatalytic activity of hydrous oxides of aluminium deliberately deposited on the TiO 2 surface. Silica, also, may be present in freshwater [12], often as a silica-alumina species [13]. Therefore, the effects of adsorbed silica are compared with those of adsorbed alumina.…”
Section: Introduction and Scopementioning
confidence: 99%